Acute adverse drug reactions with contrast media after cardiac catheterization: can we identify those at risk? - Mahtta, Dhruv; Jain, Ankur; Elgendy, Islam Y. (Journal of Thoracic Disease, 2019)
Adverse reactions to contrast media are classified as acute or delayed reactions. Acute adverse drug reactions (ADRs) secondary to contrast media typically occur within 1 hour of contrast administration, as compared to within 1–7 hours for delayed reactions. ADRs have been attributed to the activation of complement and fibrinolytic systems along with the release of histamine, prostaglandins, leukotrienes, and bradykinins (1,2).